Tacrolimus combined with two different dosages of sirolimus in kidney transplantation: results of a multicenter study - Vitko, S; Wlodarczyk, Z; Kyllönen, L; Czajkowski, Z; Margreiter, R; Backman, L; Perner, F; Rigotti, P; Jaques, B; Abramowicz, D; Kessler, M; Sanchez-Plumed, J; et al. (American journal of transplantation, 2006)
Tacrolimus combined with mycophenolate mofetil (MMF) is an effective regimen in kidney transplantation. This study compared the efficacy of combining tacrolimus and two different dosages of sirolimus with an established tacrolimus-MMF regimen. Each day in addition to tacrolimus, 325 patients received 2 mg sirolimus (TAC-SRL2 mg), 325 patients received 0.5 mg sirolimus (TAC-SRL0.5 mg) and 327 patients 1 g MMF (TAC-MMF). The initial tacrolimus dose was 0.2 mg/kg/day. Sirolimus patients received loading doses of 6 or 1.5 mg, and daily doses of 2 or 0.5 mg thereafter. Steroid administration was identical for all groups. The incidence of biopsy-proven acute rejection was lower in the TAC-SRL2 mg group (15.7%) compared with the TAC-SRL0.5 mg (25.2%, p = 0.003) and the TAC-MMF groups (22.3%, p = 0.036). Six-month graft survival was 91.0% (TAC-SRL2 mg), 92.6% (TAC-SRL0.5 mg) and 92.4% (TAC-MMF); the respective values for patient survival were 98.1%, 97.8% and 97.9%. Thirty-four patients (10.5%), 19 patients (5.8%) and 16 patients (4.9%) in the TAC-SRL2 mg, TAC-SRL0.5 mg and TAC-MMF groups, respectively, discontinued the study because of adverse events. Hyperlipemia was reported more often in the TAC-SRL2 mg group (24.0%) compared with 19.4% (TAC-SRL0.5 mg) and 11.0% (TAC-MMF; p < 0.05). Combining 2 mg sirolimus/day with tacrolimus results in lower rates of acute rejection, but a higher incidence of adverse events.
Keywords: Biopsy; Humans; lidé středního věku; následné studie; Graft Rejection; Dose-Response Relationship, Drug; Female; dospělí; Sirolimus; výsledek terapie; sirolimus; lidé; Australia; Europe; imunosupresiva; biopsie; Adult; Immunosuppressive Agents; transplantace ledvin; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; incidence; Incidence; Treatment Outcome; Tacrolimus; Kidney Transplantation; vztah mezi dávkou a účinkem léčiva; takrolimus; míra přežití; mužské pohlaví; kombinovaná farmakoterapie; Austrálie; Evropa; rejekce štěpu; Drug Therapy, Combination; Survival Rate